Population, land tenure, and natural resource management: the case of customary land area in Malawi - Place, Frank; Otsuka, Keijiro (International Food Policy Research Institute, 1997)
This paper uses cross section-time series data on 57 communities in Malawi to determine statistically the factors determining changes in land use, tree cover, and crop yield. The econometric model is developed from a theoretical model which also endogenizes population growth and prevailing land tenure institutions within the customary sector of Malawi. The analysis reflects changes between 1971 and 1995, utilizing aerial photos taken at these dates and complementing these with field surveys. The data show a deterioration of Malawi's natural resource base: declining yields, loss of tree cover, and near exhaustion of land for agricultural expansion. Key findings are that population pressure induces land conversion but not yield or tree cover change; the matrilocal system of household residence is negatively associated with tree cover but induces agricultural conversion; and there is some improvement in management of resources as their scarcity increases. Policy recommendations include greater focus on agroforestry to increase tree cover as woodland areas are poorly managed, and increased effort to improve market integration since this benefits crop yields without adverse effects on tree cover.